Pengaruh Self Control, Cyberloafing, dan Emotional Exhaustion terhadap Job Performance Gen Z di Kota Bima - Nurhaliza, Ana; Jaenab, Jaenab; Hidayanti, Mawar (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
The purpose of this study was to examine the effect of self-control, cyberloafing and emotional exhaustion on the job performance of gen z in Bima City. This study is a quantitative study and the type of research is associative. The population in this study amounted to 100 generation z employees and the sampling technique used purposive sampling technique. The data collection technique used a questionnaire, referring to a 5-point Likert scale then distributed to 100 respondents of gen z employees in Bima City offline and online. The data analysis technique used the SPSS 2016 application. With the stages of conducting validity tests, reliability tests, classical assumption tests consisting of (normality tests, multicollinearity tests, heteroscedasticity tests and autocorrelation tests) then continued with multiple linear regression tests, multiple correlation coefficient tests, determination coefficient tests, t tests and F tests. The results of this study: 1) Self Control shows a significant effect on the job performance of gen z in Bima City. 2) Cyberloafing shows no significant effect on the job performance of gen z in Bima City. 3) Emotional Exhaustion shows no significant effect on Gen Z job performance in Bima City. 4) Self-control, Cyberloafing and Emotional exhaustion have a significant effect on Gen Z job performance in Bima City.